Gene structures, classification and expression models of the AP2/EREBP transcription factor family in rice - Sharoni, Akhter Most; Nuruzzaman, Mohammed; Satoh, Kouji; Shimizu, Takumi; Kondoh, Hiroaki; Sasaya, Takahide; Choi, Il-Ryong; Omura, Toshihiro; Kikuchi, Shoshi (Plant and cell physiology, 2011)
We identified 163 AP2/EREBP (APETALA2/ethylene-responsive element-binding protein) genes in rice. We analyzed gene structures, phylogenies, domain duplication, genome localizations and expression profiles. Conserved amino acid residues and phylogeny construction using the AP2/ERF conserved domain sequence suggest that in rice the OsAP2/EREBP gene family can be classified broadly into four subfamilies [AP2, RAV (related to ABI3/VP1), DREB (dehydration-responsive element-binding protein) and ERF (ethylene-responsive factor)]. The chromosomal localizations of the OsAP2/EREBP genes indicated 20 segmental duplication events involving 40 genes; 58 redundant OsAP2/EREBP genes were involved in tandem duplication events. There were fewer introns after segmental duplication. We investigated expression profiles of this gene family under biotic stresses [infection with rice viruses such as rice stripe virus (RSV), rice tungro spherical virus (RTSV) and rice dwarf virus (RDV, three virus strains S, O and D84)], and various abiotic stresses. Symptoms of virus infection were more severe in RSV infection than in RTSV and RDV infection. Responses to biotic stresses are novel findings and these stresses enhance the ability to identify the best candidate genes for further functional analysis. The genes of subgroup B-5 were not induced under abiotic treatments whereas they were activated by the three RDV strains. None of the genes of subgroups A-3 were differentially expressed by any of the biotic stresses. Our 44K and 22K microarray results suggest that 53 and 52 non-redundant genes in this family were up-regulated in response to biotic and abiotic stresses, respectively. We further examined the stress responsiveness of most genes by reverse transcription-PCR. The study results should be useful in selecting candidate genes from specific subgroups for functional analysis.